The effect of changing marginal-cost to physical-order dispatch in the power sector - Raúl Gutiérrez-Meave; Juan Rosellón; Luis Sarmiento (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
The analysis of local environmental policies is essential when evaluating the consistency of national public policies vis-à-vis the compliance of global agreements to reduce climate change. This study explores one of these policies; the 2021 Mexican reform to change electric power dispatch from a marginal-cost-based to a command and control physical system prioritizing power generation from the state power company. The new law forces the dispatch of the state company power facilities before private power producers. We use the GENeSYS-MOD techno-economic model to determine the reform's effect on the power system's generation mix, cost structure, and anthropogenic emissions. For this, we optimize the model under three distinct scenarios; a business-as-usual scenario with no changes to the merit order, a model with the new physical order dispatch, and an additional case where in addition to the shift to the physical dispatch, we reduce the price of fuel oil below natural gas prices to simulate the current behavior of the power company. It is relevant to note that we optimize the energy system without any assumption regarding renewable targets or climate goals because of political uncertainty and the need of pinpoint the effect of the merit order change while avoiding possible variations in the state-space arising from other constraints. Our results show that by 2050, the new dispatch rule increases the market power of the state company to 99% of total generation and decreases the share of renewable technologies in the generation mix from 72% to 51%. Additionally, cumulative power sector emissions increase by 563 Megatons of CO2, which with the current cost of carbon in the European Emissions Trading System translates to around 36 billion Euros.
Keywords: Q42; Q47; Q48; 330; Merit Order Rules; Power Sector; Energy Reform; Mexico; GENeSYS-MOD